UJI PERBEDAAN MEDIA DAN KONSENTRASI BAP TERHADAP PERTUMBUHAN TUNAS PISANG RAJA SECARA KULTUR IN VITRO - Lucky Prayoga; Sugiyono Sugiyono (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2010)
A research with aims of obtaining which better between MS and Gamborg (B5) as the media in raja banana in vitro culture and knowing how much BAP needed in order to gain a most optimal growth of raja banana in in vitro culture. The research has been done in Plant Physiology Laboratory Biology Faculty General Soedirman University from April up to July 2010. Completely Randomized Design has been used with split plot design. As the main plot were media; i.e. MS media (M1) and Gamborg (B5) media (M2). As the sub plot were BAP concentration (K); consist of K0: 0 2M, K1: 5 2M, K2: 10 2M, K3: 15 2M, K4: 20 2M and K5: 25 2M. Each treatment repeated three times and each repeating treatments consist of three sub-samples. It could be concluded from the result that raja banana in vitro culture might be done in MS or Gamborg (B5) media. The best concentration of BAP in stimulating the forming and the growth of raja banana shoots in in vitro culture was 15 2M. Key words : BAP, Gamborg (B5) medium, MS medium, Raja banana shoot raja